2014
DOI: 10.3997/2214-4609.20141825
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Information in Ill-posed Inverse Problems

Abstract: SUMMARYIt is well known that parameter updating of large-scale numerical reservoir flow models (a.k.a. 'computer assisted history matching') is an ill-posed inverse problem. Typically the number of uncertain parameters in a reservoir flow model is very large whereas the available information for estimating these parameters is limited. The classic solution to this problem is to regularize the unknowns, e.g. by penalizing deviations from a prior model. Attempts to estimate all uncertain parameters from productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…They argued, by use of numerical examples, that localized unrealistic-parameter values can be used as an indicator of model errors in the underlying reservoir model, a concept that they named "model maturation." In a follow-up study, Kahrobaei et al (2014) showed that the application of unregularized reservoir-parameter estimation may sometimes give an indication of the location of significant missing features in the model. In the present study we further analyze this phenomenon by addressing the identifiability of flow-relevant features.…”
Section: Introductionmentioning
confidence: 99%
“…They argued, by use of numerical examples, that localized unrealistic-parameter values can be used as an indicator of model errors in the underlying reservoir model, a concept that they named "model maturation." In a follow-up study, Kahrobaei et al (2014) showed that the application of unregularized reservoir-parameter estimation may sometimes give an indication of the location of significant missing features in the model. In the present study we further analyze this phenomenon by addressing the identifiability of flow-relevant features.…”
Section: Introductionmentioning
confidence: 99%